2022
DOI: 10.3390/jcm11061665
|View full text |Cite
|
Sign up to set email alerts
|

Response Assessment to Erythropoietin-Zeta (Epo-Alpha Biosimilar) Therapy in Low-Risk Myelodysplastic Syndromes

Abstract: Background. This prospective observational study aimed to verify the efficacy of erythropoietin zeta in the treatment of patients with low-risk myelodysplastic syndrome. Methods. Patients with low/int-1 IPSS risk and serum erythropoietin level below 500 U/L were enrolled. Treatment consisted of erythropoietin zeta 40,000 U subcutaneously once a week. The primary endpoint was the erythroid response. According to Simon’s two-stage statistical design, 36 patients were recruited. The median age was 75 years (range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In particular, evidence from studies in MDS showed that B‐ESA were similar in terms of efficacy and safety to originator epoetin agents, as reported by a recent study in elderly MDS patients treated with B‐ESA alpha 23 and a larger meta‐analysis 24 . Recently, Vetro et al reported the efficacy and safety data in the management of anemia within a prospective study of 36 patients with low‐risk MDS who received B‐ESA zeta at a dose of 40 000 U/week administered subcutaneously 25 . An erythroid response was achieved in 50% and 75% of patients, respectively, after 8 and 16 weeks of treatment, with five patients requiring a doubling of the weekly B‐ESA dose to achieve AR.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…In particular, evidence from studies in MDS showed that B‐ESA were similar in terms of efficacy and safety to originator epoetin agents, as reported by a recent study in elderly MDS patients treated with B‐ESA alpha 23 and a larger meta‐analysis 24 . Recently, Vetro et al reported the efficacy and safety data in the management of anemia within a prospective study of 36 patients with low‐risk MDS who received B‐ESA zeta at a dose of 40 000 U/week administered subcutaneously 25 . An erythroid response was achieved in 50% and 75% of patients, respectively, after 8 and 16 weeks of treatment, with five patients requiring a doubling of the weekly B‐ESA dose to achieve AR.…”
Section: Discussionmentioning
confidence: 61%
“…1,7 B-ESA represent a low-cost alternative to originator erythropoietic agents in the treatment of chemotherapy-induced anemia in different oncology/hematology patients, 22 for example, in the setting of lymphoproliferative diseases and myelodysplastic syndromes (MDS). [23][24][25] In particular, evidence from studies in MDS showed that B-ESA were similar in terms of efficacy and safety to originator epoetin agents, as reported by a recent study in elderly MDS patients treated with B-ESA alpha 23 and a larger meta-analysis. 24 Recently, Vetro et al reported the efficacy and safety data in the management of anemia within a prospective study of 36 patients with low-risk MDS who received B-ESA zeta at a dose of 40 000 U/week administered subcutaneously.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations